2010
DOI: 10.1016/j.jom.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Lean principles, learning, and knowledge work: Evidence from a software services provider

Abstract: In this paper, we examine the applicability of lean production to knowledge work by investigating the implementation of a lean production system at an Indian software services firm. We first discuss specific aspects of knowledge work-task uncertainty, process invisibility, and architectural ambiguity-that call into question the relevance of lean production in this setting. Then, combining a detailed case study and empirical analysis, we find that lean software projects perform better than non-lean software pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
206
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(220 citation statements)
references
References 52 publications
10
206
0
4
Order By: Relevance
“…This is critical information, needed by managers to improve the flow of processes and hence increase customer satisfaction (Swank, 2003). Staats et al (2011) reported case-based evidence indicating that some of the technical practices (such as visualisation, standardisation and process mapping) were very effective in improving processing time and labour productivity in a software service firm. Piercy and Rich (2009) found that the elimination of NVAs through lean technical practices freed staff time, decreased lead and cycle time, reduced costs, and thus improved customer value.…”
Section: Lean Technical Practices and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…This is critical information, needed by managers to improve the flow of processes and hence increase customer satisfaction (Swank, 2003). Staats et al (2011) reported case-based evidence indicating that some of the technical practices (such as visualisation, standardisation and process mapping) were very effective in improving processing time and labour productivity in a software service firm. Piercy and Rich (2009) found that the elimination of NVAs through lean technical practices freed staff time, decreased lead and cycle time, reduced costs, and thus improved customer value.…”
Section: Lean Technical Practices and Performancementioning
confidence: 99%
“…These arguments leave service managers unclear whether lean manufacturing practices can be equally as valid for service-based processes, and substantiate the need for further research on lean system in the service context (Hadid and Mansouri, 2014;Staats et al, 2011). In response, this study seeks to answer the following question: Do lean system practices have an additive and/or non-additive (interaction) impact on operational and/or financial performance of for-profit service firms?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally designed for use in manufacturing, its principles have also been adopted in the service industry (Abdi, Shavarini & Hoseini, 2006), the public sector (Kollberg, Dahlgaard & Brehmer, 2006) and knowledge work (Staats, Brunner & Upton, 2011). Since the original coining of the term in the late 1980s (Krafcik, 1988;Womack et al, 1990), its meaning and measurement has been a hotly debated topic of inquiry.…”
Section: Lean Manufacturingmentioning
confidence: 99%
“…Increased pressure on organisations to remain competitive in terms of their product cost, service and quality, has led to the establishment of lean manufacturing as one of the most widely used production systems, as its positive impact on organisational performance and competitive advantage has been widely demonstrated (Brown et al, 2006;Cua et al, 2001;Fullerton & Wempe, 2009). As a result it has now extended beyond manufacturing into the service industry (Abdi et al, 2006), the public sector (Kollberg et al, 2006) and knowledge work (Staats et al, 2011).…”
Section: What Is Lean Manufacturing?mentioning
confidence: 99%